1996
DOI: 10.1017/s0031182000066233
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxanthine: a low molecular weight factor essential for growth of erythrocyticPlasmodium falciparumin a serum-free medium

Abstract: A low molecular weight factor in a basal medium essential for erythrocytic Plasmodium falciparum development in a serum-free medium using a cell growth-promoting factor derived from adult bovine serum was detected. The factor was hypoxanthine. The optimal hypoxanthine concentration for parasite growth was between 15 and 120 microM. The contribution of hypoxanthine to increased parasite growth was clearly evident in cultures on day 4. Among various low molecular weight supplements tested, adenine, adenosine, AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…1982;Lingnau et al, 1994;Mi-Ichi et al, 2006;Nivet et al, 1983;Ofulla et al, 1993;Willet and Canfield, 1984), the establishment of a fully-defined culture medium for the parasite has represented a major challenge. We previously reported that GFS supported intraerythrocytic growth of P. falciparum (Asahi and Kanazawa, 1994;Asahi et. al., 1996;Asahi et al, 2005).…”
Section: Cdm For Continuous Intraerythrocytic Growth Of P Falciparummentioning
confidence: 88%
See 4 more Smart Citations
“…1982;Lingnau et al, 1994;Mi-Ichi et al, 2006;Nivet et al, 1983;Ofulla et al, 1993;Willet and Canfield, 1984), the establishment of a fully-defined culture medium for the parasite has represented a major challenge. We previously reported that GFS supported intraerythrocytic growth of P. falciparum (Asahi and Kanazawa, 1994;Asahi et. al., 1996;Asahi et al, 2005).…”
Section: Cdm For Continuous Intraerythrocytic Growth Of P Falciparummentioning
confidence: 88%
“…The parasites were routinely maintained using in vitro culture techniques. The culture medium was devoid of whole serum, and consisted of basal medium supplemented with 10% GFS (Daigo's GF21; Wako Pure Chemical Industries, Japan), as previously reported (Asahi, 2009;Asahi & Kanazawa, 1994;Asahi et al, 1996;Asahi et al, 2005;Asahi et al, 2011). This complete medium is referred to as GFSRPMI.…”
Section: Parasites and Culturementioning
confidence: 99%
See 3 more Smart Citations